2006
DOI: 10.1158/1055-9965.epi-06-0446
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6-Related Genotypes, Body Mass Index, and Risk of Multiple Myeloma and Plasmacytoma

Abstract: Interleukin-6 (IL-6) promotes normal plasma cell development and proliferation of myeloma cells in culture. We evaluated IL-6 genotypes and body mass index (BMI) in a case-control study of multiple myeloma and plasmacytoma. DNA samples and questionnaires were obtained from incident cases of multiple myeloma (n = 134) and plasmacytoma (n = 16; plasma cell neoplasms) ascertained from the Los Angeles County population-based cancer registry and from siblings or cousins of cases (family controls, n = 112) and popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
68
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 49 publications
7
68
2
Order By: Relevance
“…In conclusion, the present findings are consistent with previous reports of increasing risk of multiple myeloma with increasing BMI (6)(7)(8)(9)(10)(11). This observation has been made across both cohort (6,8,9) and case-control (7, 10, 11) studies, and in Caucasian (6-8, 10), African-American (7), and Asian (9) populations, using a single baseline or frequently updated assessment of BMI.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In conclusion, the present findings are consistent with previous reports of increasing risk of multiple myeloma with increasing BMI (6)(7)(8)(9)(10)(11). This observation has been made across both cohort (6,8,9) and case-control (7, 10, 11) studies, and in Caucasian (6-8, 10), African-American (7), and Asian (9) populations, using a single baseline or frequently updated assessment of BMI.…”
Section: Discussionsupporting
confidence: 92%
“…The present findings are therefore consistent with the published literature. Of interest, the previous studies relied on a single (enrollment) classification of BMI (6)(7)(8)(9)(10)(11). The similarity of the present report with those studies argues against an important effect of misclassification of BMI on the prior findings.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Interleukin-6 promotes normal plasma cell development and proliferation of myeloma cells in culture, and has been associated with an increased risk of plasma cell neoplasms. 45 Cozen et al found that the variant allele of the interleukin promoter single nucleotide polymorphism -572 was associated with a 2-fold increased risk of plasma cell neoplasms, compared to the risk in family and population controls. 45 Increased concentrations of interleukin-6 and interleukin-12 were also found in blood plasma, culture supernatant and isolated and broken lymphocytes from patients with B-CLL.…”
mentioning
confidence: 99%